A realist impact evaluation of a tool to strengthen equity in local government policy-making - Sally Schultz; Felicity Beissmann; Christina Zorbas; Serene Yoong; Anna Peeters; Kathryn Backholer (BMC, 2024)
Abstract Background Local governments have a critical role to play in addressing health inequities. Health equity impact assessments are recommended to help governments apply an equity lens to the development and implementation of policies and programs. Despite evidence of equity-positive benefits of such tools, adoption remains limited, prompting calls for evaluations to assess their impact and identify factors that will promote uptake across various contexts. Methods We conducted a mixed method study to evaluate the impact of an equity impact assessment (EIA) tool and process on policies and organisational capacity in a local government in Victoria, Australia, and identify factors that influenced this impact. We analysed 33 documents related to 18 EIAs, and conducted surveys (n = 40) and in-depth interviews (n = 17) with staff involved in EIAs. Results Almost all (17 of 18) EIAs resulted in equity-positive changes to policies and programs, most frequently addressing individual-level factors, such as making community communications and consultations more accessible to under-represented or under-served groups. Structural-level recommendations from one EIA, such as increasing diversity in decision-making panels, were found to impact both the current policy and a broad range of future, related projects and services. Improvements in equity-centric organisational culture and capacity (including staff awareness, skills and confidence) and increased engagement with under-represented communities were also reported. Factors perceived to influence the impact of EIA's related to organisational commitment and capacity to prioritise equity, process-level factors related to the type and timing of EIAs, and extent of implementation support. Conclusion Our study supports wider uptake of health equity impact assessments in local government policies and programs. Legislation, leadership and resources from upper-tiers of government can help increase the adoption of equity tools to reduce disparities in population health.